WHAT ANIMAL CANCERS TEACH US ABOUT HUMAN BIOLOGY - Kattner, Patricia; Zeiler, Katharina; Herbener, Verena J.; Ferla-Brühl, Katia La; Kassubek, Rebecca; Grunert, Michael; Burster, Timo; Brühl, Oliver; Weber, Anna Sarah; Strobel, Hannah; Karpel-Massler, Georg; Ott, Sibylle; et al. (Theranostics, 2021)
Cancers in animals present a large, underutilized reservoir of biomedical information with critical implication for human oncology and medicine in general. Discussing two distinct areas of tumour biology in non-human hosts, we highlight the importance of these findings for our current understanding of cancer, before proposing a coordinated strategy to harvest biomedical information from non-human resources and translate it into a clinical setting. First, infectious cancers that can be transmitted as allografts between individual hosts, have been identified in four distinct, unrelated groups, dogs, Tasmanian devils, Syrian hamsters and, surprisingly, marine bivalves. These malignancies might hold the key to improving our understanding of the interaction between tumour cell and immune system and, thus, allow us to devise novel treatment strategies that enhance anti-cancer immunosurveillance, as well as suggesting more effective organ and stem cell transplantation strategies. The existence of these malignancies also highlights the need for increased scrutiny when considering the existence of infectious cancers in humans. Second, it has long been understood that no linear relationship exists between the number of cells within an organism and the cancer incidence rate. To resolve what is known as Peto's Paradox, additional anticancer strategies within different species have to be postulated. These naturally occurring idiosyncrasies to avoid carcinogenesis represent novel potential therapeutic strategies.
Keywords: Type of access: Open Access; infectious tumour; transmissible cancer; Peto's paradox; anticancer mechanisms; non-human malignancies; paediatric cancer